Light-regulated voltage-gated potassium channels for acute interrogation of channel function in neurons and behavior. - Henry H Jerng (PLoS ONE, 2021)
Voltage-gated potassium (Kv) channels regulate the membrane potential and conductance of excitable cells to control the firing rate and waveform of action potentials. Even though Kv channels have been intensely studied for over 70 year, surprisingly little is known about how specific channels expressed in various neurons and their functional properties impact neuronal network activity and behavior in vivo. Although many in vivo genetic manipulations of ion channels have been tried, interpretation of these results is complicated by powerful homeostatic plasticity mechanisms that act to maintain function following perturbations in excitability. To better understand how Kv channels shape network function and behavior, we have developed a novel optogenetic technology to acutely regulate Kv channel expression with light by fusing the light-sensitive LOV domain of Vaucheria frigida Aureochrome 1 to the N-terminus of the Kv1 subunit protein to make an Opto-Kv1 channel. Recording of Opto-Kv1 channels expressed in Xenopus oocytes, mammalian cells, and neurons show that blue light strongly induces the current expression of Opto-Kv1 channels in all systems tested. We also find that an Opto-Kv1 construct containing a dominant-negative pore mutation (Opto-Kv1(V400D)) can be used to down-regulate Kv1 currents in a blue light-dependent manner. Finally, to determine whether Opto-Kv1 channels can elicit light-dependent behavioral effect in vivo, we targeted Opto-Kv1 (V400D) expression to Kv1.3-expressing mitral cells of the olfactory bulb in mice. Exposure of the bulb to blue light for 2-3 hours produced a significant increase in sensitivity to novel odors after initial habituation to a similar odor, comparable to behavioral changes seen in Kv1.3 knockout animals. In summary, we have developed novel photoactivatable Kv channels that provide new ways to interrogate neural circuits in vivo and to examine the roles of normal and disease-causing mutant Kv channels in brain function and behavior.